PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP MINAT BELI ULANG PRODUK POND’S (Studi Pada Mahasiswi Fakultas Ilmu Sosial dan Ilmu Politik Jurusan Hubungan Internasional di Universitas Mulawarman Samarinda) (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Oktavia Yolanda Lumenta, 2019.Influence Brand Image, Product Quality, and Price for Pond’s Products Repurchase Interest (Study on Students of Faculty of Social and Political Sciences at Mulawarman University of Samarinda), under the guidance of Mr. Suharno, as a first advisor and Mr. M. Amin Kadafi, as a second advisor.The purpose of this study is to investigate the impact Brand Image, Product Quality and Price on Repurchase Interest of Pond’s products. The independent variables in this study is Brand Image, Product Quality and Price, and the dependent variable is Repurchase Interest. This study was conducted on students of Faculty of Social and Political Sciences at Mulawarman University Samarinda which consists of 100 respondents.The type of research used is quantitative research. Methods of data collection using questionnaires. Data analysis used multiple linear regression. The results showed that brand image, product quality and price have a significant and positive effect on repurchase interest. The results of this study also shows that the variable of product quality perception is the dominant variable to the repurchase interest compared to other variables, namely brand image and price. Keyword : Brand Image, Product Quality, Price and Repurchase Interest